Contribution of the Application of Learning Methods and Learning Activities to the Results of Islamic Religious Education of SMP Swasta Sei Bejangkar - Rusydi Ananda; Muhammad Iskandar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to identify and describe: (1) the positive and significant contribution of the application of the learning method to the learning outcomes of Islamic Religious Education, (2) the positive and significant contribution of learning activities to the learning outcomes of Islamic Religious Education, and (3) the positive and significant contribution of the application. Learning methods and learning activities together on the learning outcomes of Islamic Religious Education?.The research was conducted at the Sei Bejangkar Region Private Junior High School. This research is a quantitative study with a correlation research method. The population in this study was all students of class VIII which consisted of 2 classes with a total of 72. All students were used as research samples. The data collection instruments used was questionnaires and tests. The data analysis used is correlation and regression. The research findings show: (1) there is a positive and significant contribution between the application of learning methods and learning outcomes with a correlation number of 0.354 with the regression line equation Ŷ = 71.60 + 0.23 X1, (2) there is a positive and significant contribution between learning activities and outcomes. Learn with the correlation number 0.473 with the regression line equation Ŷ = 68.96 + 0.28X2. and (3) there is a positive and significant contribution between the application of learning methods and learning activities with learning outcomes with a correlation number of 0.549 with the regression line equation Ŷ = 138.80 + 0.18X1 + 0.25X2. The effective contribution of the variable application of learning methods to learning outcomes is 9.90%, while the effective contribution of learning activity variables to learning outcomes is 20.00%.